2022
DOI: 10.21203/rs.3.rs-2075224/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sperm quality and fertility of Murrah and Nili-Ravi bulls compared with indigenous buffalo bulls in Bangladesh

Abstract: Fresh and frozen semen quality of Murrah and Nili-Ravi bulls in comparison with indigenous buffalo bulls was evaluated by Computer Assisted Sperm Analyzer (CASA). Semen was collected regularly once a week semen collection schedule from six (two/group) buffalo bulls. Fresh semen was evaluated for sperm concentration, motility, sperm kinematics, morphology and dose/ejaculate. Semen was diluted in a commercial extender (AndroMed), equilibrated, cryopreserved and finally evaluated for post-thaw sperm quality. On-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
1
1
Order By: Relevance
“…The similar findings were also reported for Nili Ravi (4.67±1.62 ml) buffalo bulls (Muhammad et al, 2000). A non-significant and lower estimate of per ejaculate semen volume in Murrah and Nili Ravi buffalo bulls (3.04±1.81 and 2.67±0.44 ml, respectively) were reported by Miraz et al (2022). As compared to our study, higher estimates of semen volume were reported by Khatun et al (2013) in Murrah (5.50±0.176 ml) and crossbred cattle (5.81±0.176 ml) bulls.…”
Section: Resultscontrasting
confidence: 88%
See 1 more Smart Citation
“…The similar findings were also reported for Nili Ravi (4.67±1.62 ml) buffalo bulls (Muhammad et al, 2000). A non-significant and lower estimate of per ejaculate semen volume in Murrah and Nili Ravi buffalo bulls (3.04±1.81 and 2.67±0.44 ml, respectively) were reported by Miraz et al (2022). As compared to our study, higher estimates of semen volume were reported by Khatun et al (2013) in Murrah (5.50±0.176 ml) and crossbred cattle (5.81±0.176 ml) bulls.…”
Section: Resultscontrasting
confidence: 88%
“…The least square means for post thaw motility were found to be 47.465±0.016% and 42.052±0.019%, in Murrah and Nili Ravi buffalo bulls, respectively (Table 2). Miraz et al (2022) also observed a significant effect (P<0.01) of breed on post thaw motility in buffalo (Indigenous, Murrah and Nili Ravi) bulls.…”
Section: Resultsmentioning
confidence: 66%